Adoption of Maize Seed and Storage Technology by Low-Income Farmers in Mexico and Malawi - Guevara Alvarez, Gloria. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: William Masters.; Committee: Shibani Ghosh, and Jason Donavan .; Keyword: Agriculture economics.